Pendidikan Kesehatan Reproduksi di SMP 1 Samboja (Perspektif Fiqih) - Mardati; Tutik Hamidah (HMPS Tadris Biologi FTIK IAIN Jember, 2021)
This study aims to determine: 1) the implementation of reproductive health education in SMP 1 Samboja; 2) Reproductive health education in terms of fiqh perspective. This research is a descriptive qualitative research with case study method. The results of the study show that reproductive health education that has been held by the PKPR Samboja Health Center at SMP 1 Samboja is a form of concern for adolescents considering that there is still a lack of awareness of students about reproductive health and even the need for an early introduction to reproductive health. The focus of reproductive health education provided by PKPR is the provision of reproductive health education and the introduction of reproductive diseases. And follow-up efforts are carried out in the form of monitoring adolescent health by cadres of PTM (Non-Communicable Diseases), UKS cadres (School Health Unit) and youth counselors. In the view of Islam, basically the norms of sexuality and reproduction have been contained in various books of Fiqh as a source for realizing the goals of Islamic law, namely maintaining honor and self-respect, as well as maintaining the sanctity of offspring and reproductive rights properly. This shows that Islam always prioritizes to aspects of behavior and lifestyle to realize human reproductive health. Keywords: fiqh perspective, reproductive health Penelitian ini bertujuan untuk mengetahui: 1) Implementasi pendidikan kesehatan reproduksi di SMP 1 Samboja; 2) Pendidikan kesehatan reproduksi ditinjau dari perspektif fiqih. Penelitian ini merupakan penelitian kualitatif deksriptif dengan metode studi kasus. Hasil penelitian menujukkan Pendidikan kesehatan reproduksi yang telah diselenggarakan oleh pihak PKPR Puskesmas Samboja di SMP 1 Samboja merupakan salah satu bentuk kepedulian terhadap remaja mengingat bahwa masih minimnya kesadaran siswa-siswi tentang kesehatan reproduksi bahkan perlunya pengenalan kesehatan reproduksi sejak dini. Fokus pendidikan kesehatan reproduksi yang diberikan oleh PKPR yaitu pemberian edukasi kesehatan reproduksi dan pengenalan penyakit reproduksi. Dan upaya tindak lanjut yang dilakukan berupa pemantauan kesehatan remaja oleh kader PTM (Penyakit Tidak Menular), kader UKS (Unit Kesehatan Sekolah) dan konselor remaja. Dalam pandangan Islam pada dasarnya norma-norma seksualitas dan reproduksi telah tertuang banyak dalam berbagai kitab-kitab Fiqih sebagai sumber untuk mewujudkan tujuan syariat Islam yakni menjaga kehormatan dan harga diri, serta menjaga kesucian keturunan dan hak reproduksi dengan baik. Hal ini menujukkan bahwa Islam senantiasa memprioritaskan aspek perilaku dan gaya hidup untuk mewujudkan kesehatan reproduksi manusia. Kata kunci: kesehatan reproduksi, perspektif fiqih